2020
DOI: 10.25100/cdea.v36i66.7897
|View full text |Cite
|
Sign up to set email alerts
|

Trust as a mechanism to improve organizational performance

Abstract: This paper designs and contrasts a relational model between the trust of collaborators in organizations and the performance of the company, mediated by the organizational commitment to learning and the commitment of employees to the company. As key objectives, a double mediation model is tested in the relationship between intra-organizational trust and the firm’s performance, through the organization’s commitment to learning and the commitment of collaborators to the company. Using a 31-item survey, the goodne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Their study concluded that it is positively correlated to employees' performance. This finding is strengthened by the study of Li, et.al (2018), Li, et.al (2007), Buenaventura-Vera, and Gudziol-Vidal (2020) on the effect of organizational trust on job performance. Their studies presented scientific evidence that organizational trust predicts individual performance.…”
Section: Organizational Trust and Organizational Performancementioning
confidence: 82%
“…Their study concluded that it is positively correlated to employees' performance. This finding is strengthened by the study of Li, et.al (2018), Li, et.al (2007), Buenaventura-Vera, and Gudziol-Vidal (2020) on the effect of organizational trust on job performance. Their studies presented scientific evidence that organizational trust predicts individual performance.…”
Section: Organizational Trust and Organizational Performancementioning
confidence: 82%